Dual Ligand-Enabled Late-Stage Fujiwara–Moritani Reactions - Santiago, Carlos; Chen, Hao; Mondal, Arup; van Gemmeren, Manuel (Synlett, 2021)
In this study, we describe the use of dual ligand-based palladium catalysts for the late-stage olefination of arenes. Building upon a method previously developed for simple arenes, a variety of complex arene substrates were functionalized. Importantly, the method uses the arene as a limiting reactant and is therefore suitable for valuable starting materials that cannot be used in excess. The regioselectivity of the transformation is controlled by the steric and electronic properties of the substrate, providing access to regioisomers that would be challenging to prepare through other synthetic approaches.
Keywords: C–H bond activation; late-stage functionalization; palladium catalysis; arenes; Fujiwara–Moritani reaction; olefination